A new composite adaptive controller featuring the neural network and prescribed sliding surface with application to vibration control. (July 2018) - Phu, Do Xuan; Huy, Ta Duc; Mien, Van; Choi, Seung-Bok
Highlights: A new composite adaptive controller using two sliding surfaces in which one is the prescribed sliding surface to achieve equivalent controller is formulated. The proposed controller is implemented for vibration control of the semi-active vehicle suspension system in which MR damper is installed. The proposed control method can provide excellent vibration control performances compared with similar control strategies. Abstract: This work proposes a novel composite adaptive controller based on the prescribed performance of the sliding surface and applies it to vibration control of a semi-active vehicle seat suspension system subjected to severe external disturbances. As a first step, the online fast interval type 2 fuzzy neural network system is adopted to establish a model and two sliding surfaces are used; conventional surface and prescribed surface. Then, an equivalent control is determined by assuming the derivative of the prescribed surface is zero, followed by the design of a controller which can guarantee both stability and robustness. Then, two controllers are combined and integrated with adaptation laws using the projection algorithm. The effectiveness of the proposed composite controller is validated through both simulation and experiment by undertaking vibration control of a semi-active seat suspension system equipped with a magneto-rheological (MR) damper. It is shown from both simulation and experimental realization that excellent vibration control performances are achieved with a small tracking error between the proposed and prescribed objectives. In addition, the control superiority of the proposed controller to conventional sliding mode controller featuring one sliding surface and proportional-integral-derivative (PID) controllers are demonstrated through a comparative work.